SECONDARY SCHOOL STUDENTS' RECOUNT TEXTS: A CASE OF TRANSITIVITY ANALYSIS - Luthfi, Afdila Ula (2016)
This study aimed at investigating students' ability in writing recount texts based on its criteria and difficulties encountered in writing the texts. This study employed a case study approach. The data were six pieces of recount texts (final draft) written by eight grade students of a junior high school based on students' achievement during their study and data from interviews. The students' recount texts were analyzed based on the purpose, schematic structure and linguistic features along with the transitivity analysis. The findings show that most students were capable in writing the text in terms of schematic structures and linguistic features. All students' texts also achieved the purpose of recount text despite the failure in organizing the texts and grammatical errors found in the texts. Therefore, teachers should be more aware of students' difficulties encountered during their writing. Moreover, teachers are recommended to give feedback in the drafting phase to improve students' writing skills.;--- Penelitian ini bertujuan untuk meneliti kemampuan siswa dalam menulis teks recount berdasarkan kriteria dari teks tersebut dan kesulitan-kesulitan yang ditemui dalam menulis teks. Penelitian ini menggunakan pendekatan studi kasus. Data yang digunakan yaitu enam teks recount (draft akhir) yang ditulis oleh siswa kelas delapan berdasarkan prestasi siswa selama studi mereka dan data wawancara. Teks recount siswa dianalisis berdasarkan tujuan, struktur skematik dan fitur linguistik bersama dengan analisis transitivitas. Temuan penelitian menunjukan bahwa sebagian besar siswa mampu menulis teks recount berdasarkan struktur skematik dan fitur linguistik. Seluruh teks juga berhasil mencapai tujuan dari teks recount meskipun terdapat kegagalan dalam pengorganisasian teks dan kesalahan-kesalahan tata bahasa ditemukan didalam teks. Oleh karena itu, guru harus lebih memperhatikan kesulitan-kesulitan yang dihadapi siswa dalam menulis. Selain itu, guru dianjurkan memberikan umpan balik dalam tahap penulisan draft untuk meningkatkan kemampuan menulis siswa.